2021
DOI: 10.3390/nu13093017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Downregulates ABCA1 Expression via MEK/ERK/LXR Pathway in INS-1 Cells

Abstract: Impaired insulin secretion is one of the main causes of type 2 diabetes. Cholesterol accumulation-induced lipotoxicity contributes to impaired insulin secretion in pancreatic beta cells. However, the detailed mechanism in this process remains unclear. In this study, we proved that oxidized low-density lipoprotein (OxLDL) reduced insulin content, decreased PDX-1 expression, and impaired glucose-stimulated insulin secretion (GSIS) in INS-1 cells, which were rescued by addition of high-density lipoprotein (HDL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…We found that Rb1, Rg1, Rg3 and CK induced cholesterol e ux in TMZ-resistant GBM cells, reduced intracellular cholesterol concentrations, and redistributed lipid rafts at different levels. It has been reported that CK promoted cholesterol e ux by stimulating LXRα(Huang et al 2017;Zhou et al 2016), and we not only identi ed the increased transcription and translation of LXRα in resistant GBM cells after treated with Rg1, Rg3 and CK, but also found the induction of Rb1 and Rg1 on the expression of cholesterol e ux transporter ABCA1, whose promoter is directly bound by LXRα for transcriptional activation(Lyu et al 2021). We further observed that Rg1 and CK increased the sensitivity of resistant GBM cells to TMZ, and this effect was via upregulation of LXRα.…”
supporting
confidence: 54%
“…We found that Rb1, Rg1, Rg3 and CK induced cholesterol e ux in TMZ-resistant GBM cells, reduced intracellular cholesterol concentrations, and redistributed lipid rafts at different levels. It has been reported that CK promoted cholesterol e ux by stimulating LXRα(Huang et al 2017;Zhou et al 2016), and we not only identi ed the increased transcription and translation of LXRα in resistant GBM cells after treated with Rg1, Rg3 and CK, but also found the induction of Rb1 and Rg1 on the expression of cholesterol e ux transporter ABCA1, whose promoter is directly bound by LXRα for transcriptional activation(Lyu et al 2021). We further observed that Rg1 and CK increased the sensitivity of resistant GBM cells to TMZ, and this effect was via upregulation of LXRα.…”
supporting
confidence: 54%
“…Interestingly, in pancreatic beta cell selective ABCA1 knockout mice, the lipid content in pancreatic beta cells was increased and GSIS was impaired (6). Previously, we reported that TNF-α, angiotensin II, and oxidized low-density lipoprotein increase intracellular cholesterol content and reduce the expression of ABCA1 in pancreatic β cells [13][14][15]. We also reported that GSIS is decreased in INS-1 cells with accumulated cholesterol.…”
Section: Discussionmentioning
confidence: 88%
“…Hyperinsulinism was associated with ER stress, metainflammation, and a compensatory response of ABCA1 overexpression. On the other hand, the highly proatherogenic oxidized LDL has been described as downregulating ABCA1 expression via the MEK/ERK/LXR pathway, leading to impaired insulin synthesis and GSIS in a β-cell model [69]. Indeed, ABCA1 reduction could lead to cholesterol accumulation coupled with an increased risk of islet amyloid polypeptide (IAPP) aggregation [70], which suggests the importance of ABCA1.…”
Section: Discussionmentioning
confidence: 99%